PERANAN PROGRAM LOYALITAS ALL ACCOR LIMITLESS TERHADAP KUALITAS PELAYANAN (STUDI KASUS PADA HOTEL IBIS STYLES MEDAN) - Chafizah, Chafizah; Liyushiana, Liyushiana; Marpaung, Selviana Meldrit Monica; Renaldi, Ruri; Pramudya, Ahmad (Politeknik Bosowa, 2024)
The purpose of this study is to see how loyalty programs affect service quality at the Ibis Styles Medan. This is a qualitative study that use the case study method. Primary data and secondary data are the two categories of data used in this study. The findings of interviews with the front desk agent at the Ibis Styles Hotel Medan provided primary data, while secondary data was collected from the All Accor website. Based on the findings of the study, the following conclusions were made: 1) Provide benefits and advantages of loyalty programs that have an impact on hotel satisfaction and service quality. This is demonstrated through consumer reviews on the official All Accor website, which is used in conjunction with Trust You to calculate hotel ratings. 2) The convenience gained from the adoption of the loyalty program has an impact on increasing service quality. This is highlighted by the ease with which members of the loyalty program easily book rooms through the all accor website by inputting an e-mail address, and the front office department immediately collect guest data from room bookings which are already automatically registered in the fols system.